Performance Analysis of Islamic Banks Listed on the Indonesia Stock Exchange (IDX) Based on the Risk Based Bank Rating (RBBR) Method for the 2020-2023 Period - Syahputra, Yusuf Candra; Widodo, Moch. Wahyu (Universitas Nusantara PGRI Kediri, 2025)
Research objective: The aim of this research is to assess and examine the financial performance of Islamic banks registered on the Indonesia Stock Exchangeing (IDX) by utilizing the Risk Based on Bank Rating (RBBR) approach during the 2020-2023 timeframe. Desighn/Methode/Approaach: This research adopts a quantitative method with a descriptive approach. The study focuses on Islamic banks listed on the Indonesia Stock Exchange (IDX), including Bank Aladin Syariah, Bank Syariah Indonesia, Bank BTPN Syariah, and Bank Panin Dubai Syariah. To gather data, the documentation technique is employed, where relevant financial information is collected from the official websites of the IDX and the respective banks. The analysis in this study evaluates the performance of Islamic banks using the Risk-Based Bank Rating (RBBR) method as a key framework. Research Findings: The findings of this research present an evaluation of the financial performance of Islamic banks registered on the Indonesia Stock Exchange (IDX) from 2020 to 2023 using the Risk-Based Bank Rating (RBBR) approach. Among the banks analyzed, PT Bank Aladin Syariah Tbk exhibited notable fluctuations in its performance, with its strongest financial results recorded in 2020. These variations indicate changes in the bank's financial stability over the years, influenced by various internal and external factors.and the biggest challenges in 2022, but managed to start recovery in 2023. PT Bank Syariah Indonesia Tbk showed high stability with a